Structural behaviour of CHS T-joints subjected to brace axial compression in fire condition - Tan, Kang Hai (2015)
The structural behavior of circular hollow section (CHS) T-joints subjected to axial brace compression in fire conditions was investigated. Five full-scale tubular joints with different brace-to-chord diameter ratios were tested under elevated temperature. The tests were in isothermal heating conditions, where the specimens were heated to the desired temperatures and then subjected to static load to failure. The ultimate strength and failure modes of these joints were investigated. It was observed that both the reduction in material strength and changes in localized plastification area beneath the brace decreased the ultimate strength of the joints as temperature increased. Furthermore, local buckling and ovalisation of the chords were found to be more concentrated around the joint region at elevated temperature. To the authors’ best knowledge, these tests were among the first reported experimental investigations in the ultimate strength and failure mechanisms of tubular joints at elevated temperature. To investigate the joint behavior at high temperature in greater detail, FEM was used. The finite-element models were first validated by the test results. The development of failure mechanisms of CHS T-joints at elevated temperature was then traced with the numerical models. The models were also used to quantify the effect of elevated temperatures on three parameters that directly affect the ultimate strength of the T-joints. The three parameters are boundary condition, precompression in the chord, and chord thickness.